The effectiveness of ulcerative colitis treatment depending on the route of medical drug usage - V. O. Petryna (Zaporožskij Medicinskij Žurnal)
Aim to increase the effectiveness of ulcerative colitis (UC) treatment by combination of the basic therapy with Bifidumbacterin in microclysters with clinical and pathogenic features of the disease assessment.